Optimalisasi Manajemen Ramah Lingkungan di Desa Pasir Panjang melalui Sosialisasi Eco-Enzyme dari Sampah Organik - Meisy, Meisy; Rosani, Titik; Yunita, Herni; Liani, Mel; Meiliana, Santa; Gloria, Yohana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Improper management of organic waste can cause various environmental problems. This community service activity aims to raise awareness and skills among the residents of Pasir Panjang Village, Mempawah Timur District, Mempawah Regency in managing organic waste into eco-enzyme. The method used is socialization and training in Eco-Enzyme production for local PKK mothers. This activity is carried out through the delivery of materials and direct practice in making Eco-Enzyme. The results of the activity show an increase in participants' understanding of the benefits of household organic waste. Participants also acquire skills in processing organic waste such as fruit peels and vegetable scraps into useful and economically valuable. This activity is expected to encourage the implementation of more environmentally friendly management in Pasir Panjang Village through the use of Eco-Enzymes.